Real-world single-center data analysis of dual immunotherapy in advanced NSCLC: Efficacy, survival, and adverse events - Tao Luan; Jianqing Hao; Xiaohong Xie; Xinqing Lin; Shuaiying Wang; Baodan Yu; Qingqing Yang; Changchun Wang; Yang Luan; Gang Yang; Hanxiu Lu; Ping Sun; et al. (Human Vaccines & Immunotherapeutics, 2025)
We collected 96 patients who received dual immunotherapy between January 2019 and June 2024, in a 1:1:1 ratio based on PD-L1 expression levels of negative (<1%), medium (1% ≤ PD-L1 ≤ 49%), and high (PD-L1 ≥ 50%). This study evaluates the efficacy and safety of dual immunotherapy in patients with advanced NSCLC, stratified by PD-L1 expression levels. Among the 96 patients, the objective response rate (ORR) was 37.5%, disease control rate (DCR) was 67.8%. In the multivariate analysis of PFS, PD-L1 ≥ 50% (HR = 0.40, 95% CI: 0.22–0.74) was identified as a protective factor for PFS, while PS Score ≥ 2 (HR = 2.74, 95% CI: 1.11–6.77) and stage IV tumors (HR = 2.05, 95% CI: 1.02–4.12) were risk factors. In the multivariate analysis of OS, PD-L1 between 1% and 49% (HR = 0.51, 95% CI: 0.28–0.90) and PD-L1 ≥ 50% (HR = 0.31, 95% CI: 0.17–0.57) were protective factors, with no risk factors detected. The incidence of adverse events was 77.1%, with a 34.3% incidence of grade 3–4 immune-related adverse events. And PD-L1 ≥ 50% group adverse events incidence more common, with an overall incidence of 87.5% and a grade 3–4 incidence of 40.6%. Patients with high PD-L1 expression (≥50%) demonstrated improved progression-free survival (PFS, HR = 0.40) and overall survival (OS, HR = 0.31) but experienced a higher incidence of severe adverse events (40.6%).